Lectotypification of the name Umbilicaria africana (Umbilicariaceae, lichenized Ascomycota) - Davydov, Evgeny A.; Yakovchenko, Lidia S. (Phytotaxa, 2023)
The name Umbilicaria africana (≡Gyrophora haplocarpa var. africana), a polar-alpine lichen-forming fungus, is reviewed and lectotypified using a specimen from the Jatta collection deposited in the Herbarium Neapolitanum (NAP).